Oltre i confini di Atene: le scuole di filosofia alla fine del mondo antico - Chiaradonna, Riccardo (B@belonline, 2023)
This article focuses on philosophical schools at the end of the ancient Greco-Roman world. Under the Roman Empire, philosophy was not confined to Athens, but covered the whole Mediterranean world, especially in the East. Examples of this situation include the biography of Plotinus and the Neo-Platonist philosophical schools. A further interesting aspect of Late Antiquity is the role acquired by women in philosophical schools. Philosophy transgressed the (both geographic and cultural) boundaries of Athens and this process ensured the transmission of Greek philosophy to subsequent eras.